Multitier Programming in Hop. (Communications of the ACM, 2012)
The article discusses multitier computer application programming for servers and clients on web-based platforms using the Hop programing language from the National Institute for Research in Computer Science and Control (INRIA) in France. Topics include Cascading Style Sheets (CSS), widgets, and potential applications of Hop coding in smartphones and location-based software. Examples of code written in Hop are presented. Other programing languages mentioned include JavaScript, HyperText Markup Language (HTML), and multitier programing languages including Links, from the University of Edinburgh, and Google Web Toolkit (GWT), from Internet services provider Google.